(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
Reliable DC power is essential for the continuous operation of battery energy storage systems (BESS) in EV systems. Since these systems require a specific voltage level that many sources cannot directly provide, an efficient voltage-boosting stage is necessary. This paper presents a higher-voltage-gain structure for a non-isolated DC/DC converter with a switched-inductor-based double-switch configuration to step up a low input voltage to a stable high output suitable for EV applications. The proposed converter is analyzed using MATLAB/Simulink to evaluate voltage gain, efficiency, and device stresses. A 100 W hardware prototype producing 200 V output is developed for validation. Both simulation and experimental results confirm improved voltage regulation and reduced output ripple under varying duty conditions. Overall, the topology provides a practical and efficient solution for EV battery energy storage systems.